Les nouveaux internats d’éducation prioritaire. Apports et limites de dispositifs pédagogiques contemporains d'accompagnement scolaire - Laurent Lescouarch; Filippo Pirone (Recherches en Éducation)
In this paper we analyse the pedagogical pattern offered by those boarding schools which have recently been created in education action zones as a new school support shape. If under official texts they are supposed to grant an ideal educational environment for students coming from disadvantaged social and cultural backgrounds, these boarding schools aim at reinternalizing learning activities which have been externalised from educational system for a long time. Our analyses lean on a pedagogical and sociological survey focalised on the effective implementation in these boarding schools of school support activities aiming at socializing students to school work and to “being a student”. We have also analysed how school actors daily mobilise these activities. The results of this survey show that these new boarder schools share with contemporary school support projects the same limits: not very effective in ensuring continuity between transmission and learning, they mostly remain beneficial only to those students which already own some socio-cognitive dispositions as pedagogical autonomy and familiarity with school culture.